IMPORTANCE OF KINETIN FOR SOME GROWTH CHARACTERS OF Zea mays L. UNDER WATER STRESS CONDITION - & Ahmed, Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A field experiment was conducted during two seasons Spring and Autums 2014 at the expermeatal field of Field crop Department, College of Agriculture, University of Baghdad to study the importance of Kinetin for some traits of Zea mays L. under water stress condition , by using randomized complete Block Design in the arrangement of a split-plot with three replications . Skipping irrigation elongation T2, emergence of aers T3, 10% flowering feminization T4, milk stage T5, and dough stage T6 . All these treatments were irrigated when 85% of the available water was depleted with control treatment T1 which was irrigated when 50% of the available water was depleted , were assigned as a main plots while the Kinetin spray in the six and ten leaves stages K1,K2 in addition to without spray K0 treatment were assigned as a sub-plots. The results showed that Skipping irrigation at Elongation, and 10% flowering feminization led to lower average plant height, leaf area , leaf area indx , Dry matter yield , growth rate and the dry weight of the root. The plant spray with Kinetin at ten leaves stage gave the highest average of plant height(160.8 , 157.09 cm) , leaf area (5783 , 5872 cm2) , leaf area index (4.13 , 4.19 ) , plant dry weight (186.26 , 196.05 gm.plant-1) , crop growth rate (16.83 , 20.89 (gm.m2)-1.day-1) and root dry weight (26.14 , 26.77 gm.plant-1) for both season respectively . Therefor we recomned the necessity to irrigate in the following stages Elongation, emergence of Areanas, and specialy 10% flowering feminization , in addition to possibility of spray Zea mays plant with kinetin to improre tolerate of water stress.